Measuring the factors influencing job satisfaction in the garment industry: Bangladesh perspectives - Ramachandaran, Sharmila Devi; Vasudevan, Asokan; Tinagaran, Rajermani; Subra, Kumarashvari (International Journal of Management and Sustainability, 2024)
The research aims to examine the influence of employee job satisfaction within the garment industry. Utilizing quantitative methodology, the study focuses on collecting numerical data amenable to statistical analysis, with subsequent data transformation through quantitative tools to identify factors impacting employee job satisfaction. Questionnaires were disseminated online, affording respondents flexibility in their participation. Employing non-probability sampling, individuals in the garment industry aged 18 to 40 were surveyed. Through SPSS, a series of hypotheses derived from a theoretical model of turnover intention underwent empirical testing. The study’s findings reveal that employee job satisfaction is significantly affected by several factors, including salary and benefits, supervisory conduct, and organizational policies. This research provides valuable insights for employers and policymakers, facilitating a comprehensive understanding and the development of strategies aimed at enhancing employee satisfaction. Each of these groups stands to gain invaluable insights and practical applications from the study’s findings, with the potential to drive positive change in the workplace and the industry. Ultimately, these efforts are anticipated to positively influence the overall performance of the garment industry. Furthermore, this study’s novel approach to exploring employee job satisfaction within the garment industry is expected to contribute significantly to the existing body of knowledge in the field, paving the way for further research and facilitating more effective strategies for industry enhancement.